The Design and Methodology of the Ohio COVID-19 Survey - Marcus E. Berzofsky; Naomi Freedner; Caroline Scruggs; Robert Ashmead; Timothy Sahr; Bo Lu; Michael Nau; Eric Seiber; Hilary Rosebrook; Tom Duffy (Ohio Journal of Public Health, 2021)
Background: Governments worldwide are balancing contrasting needs to curtail the toll that coronavirus disease 2019 (COVID-19) takes on lives and health care systems and to preserve their economies. To support decisions, data that simultaneously measure the health status of the population and the economic impact of COVID-19 mitigation strategies are needed. In the United States, prior to the onset of COVID-19, surveys or tracking systems usually focused on public health or economic indicators, but not both. However, tracking public health and economic measures together allow policy makers and epidemiologists to understand how policy and program decisions are associated. The Ohio COVID-19 Survey (OCS) attempts to track both measures in Ohio as one of the first statewide population surveys on COVID-19. To achieve this there are several methodological challenges which need to be overcome. Methods: The OCS utilizes a representative panel offering both cross-sectional and longitudinal analyses. It targets 700 to 1000 respondents per week for a total of 12 600 to 18 000 respondents over an 18-week period. Leveraging a sample of 24 000 adult Ohioans developed from a statewide population health survey conducted in fall 2019, the OCS produces weekly economic and health measures that can be compared to baseline measures obtained before the COVID-19 pandemic began. Results: The OCS was able to quickly launch and achieve high participation (45.2%) and retention across waves. Conclusion: The OCS demonstrates how it is possible to leverage an existing health-based survey in Ohio to generate a panel which can be used to quickly track fast-breaking health issues like COVID-19.
Keywords: COVID-19; Panel survey; Survey design; Ohio COVID-19 survey